RabGAP AS160/TBC1D4 deficiency increases long-chain fatty acid transport but has little additional effect on obesity and metabolic syndrome in ADMSCs-derived adipocytes of morbidly obese women - Mikłosz, Agnieszka; Łukaszuk, Bartłomiej; Supruniuk, Elżbieta; Grubczak, Kamil; Kusaczuk, Magdalena; Chabowski, Adrian (Frontiers in Molecular Biosciences, 2023)
The Akt substrate of 160 kDa (AS160), also known as TBC1 domain family member 4 (TBC1D4), represents a crucial regulator of insulin-stimulated glucose uptake in skeletal muscle and adipose tissue. Recent evidence suggests that AS160/TBC1D4 may also control the cellular entry of long-chain fatty acids (LCFAs), resulting in changes to the lipid profile of muscles and fat cells in lean subjects. However, there are virtually no data on AS160/TBC1D4 expression and its modulatory role in lipid metabolism in the adipocytes from morbidly obese individuals of different metabolic status. In this study, we evaluated the effect of the three main factors, i.e., AS160 silencing, obesity, and metabolic syndrome on lipid uptake and profile in fully differentiated adipocytes derived from mesenchymal stem cells (ADMSCs) of lean and obese (with/without metabolic syndrome) postmenopausal women. Additionally, we tested possible interactions between the explanatory variables. In general, obesity translated into a greater content of fatty acid transporters (especially CD36/SR-B2 and SLC27A4/FATP4) and boosted accumulation of all the examined lipid fractions, i.e., triacylglycerols (TAGs), diacylglycerols (DAGs), and free fatty acids (FFAs). The aforementioned were further enhanced by metabolic syndrome. Moreover, AS160 deficiency also increased the abundance of SLC27A4/FATP4 and CD36/SR-B2, especially on the cell surface of the adipocytes derived from ADMSCs of subcutaneous deposit. This was further accompanied by increased LCFA (palmitic acid) uptake. Despite the aforementioned, AS160 silencing seemed unable to significantly affect the phenotype of the adipocytes stemming from obese patients with respect to their cellular lipid profile as we observed virtually no changes in TAG, DAG, and FFA contents when compared to cells with the reference level of proteins. Nevertheless, knockdown of AS160 stimulated fatty acid oxidation, which may indicate that adaptive mechanisms counteract excessive lipid accumulation. At the same time, adipocytes of visceral origin were rather insensitive to the applied intervention.